THE ROLE OF MARKETING MANAGEMENT IN BUILDING LONG-TERM CUSTOMER VALUE (LITERATURE REVIEW) - Fitriyani, Syabrina; Tukiran, Martinus (International Journal of Multidisciplinary Research and Literature, 2024)
This study aims to analyze the role of marketing management in building long-term customer value through a systematic approach to literature study. The results show that modern technologies, such as artificial intelligence (AI), metaverse marketing, and digital strategies, such as social media and omnichannel marketing, significantly increase customer engagement, loyalty, and trust. Customer Relationship Management (CRM) effectively increases customer lifetime value (CLV) by up to 30%, while digital personalization increases customer engagement by 42%. In addition, personalized value propositions play an important role in strengthening customer relationships and creating immersive experiences. This study affirms that utilizing technology, personalization, and relationship-oriented strategies is essential in contemporary marketing management. These findings provide an important contribution to understanding how strategic approaches can support the development of long-term customer value, increase retention, and strengthen customer loyalty in the digital era